Barbaloin Treatment Contributes to the Rebalance of Glucose and Lipid Homeostasis of Gestational Diabetes Mellitus Mice - Yong Wang; Haiying Wang; Fengzhen Yang (SAGE Publishing, 2020)
Aloe vera L has been shown to possess hypoglycemic and hypolipidemic effects on type 2 diabetic patients, and its major benefits may be linked to barbaloin, which is a major component of Aloe vera L. This study focused on investigating the potential effects and underlying mechanisms of barbaloin on gestational diabetes mellitus (GDM). The db/+ diabetic mice with GDM were daily orally administered with barbaloin or metformin during the gestational period. The results demonstrated that administration of barbaloin significantly reduced blood glucose levels and increased insulin levels in GDM mice. We further found that barbaloin treatment reduced inflammatory response and ROS levels in the liver. Finally, we revealed that the AMP-activated protein kinase (AMPK) / peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) signaling pathway was involved in BAT-mediated beneficial effects on mice with GDM. Our study suggested that barbaloin exerted hypoglycemic and hypolipidemic effects on GDM mice, via, at least in part, modulation of AMPK/ PGC-1α signaling in GDM mice.